Love Thy Patient: Justice, Caring, and the Doctor–Patient Relationship - Rhodes, Rosamond (Cambridge quarterly of healthcare ethics, 1995)
Traditional moral theories of rights and principles have dominated medical ethics discussions for decades. Appeals to utilitarian consequences, as well as the principles of respect for autonomy, beneficence, and justice, have provided the standard vocabulary and filled the literature of the field.Recently on the bioethics scene, however, there has been some discussion of virtue, and, particularly within the nursing ethics literature, appeals are being made to the feminist ethics of care. This intimation of a shift in the wind may have to do with postmodern doubt, or it may be attributable to the claim that virtue theory and the ethics of care (which focus on the character or feelings of the agent, respectively) are more appropriate to private interaction; theories of rights and justice (which focus on the act rather than the agent) are best applied to the political domain of public policy.